Analisis Dampak Masa Pandemi Dan New Normal Terhadap Pedagang Kaki Lima (LoSaPa) Lontong Sayur Padang Pasar Tradisional 16 Ilir Kota Palembang - Rika Fitri Ramayani; Emi Sukmawati (Journal of Economic, Bussines and Accounting (COSTING), 2021)
One of the street vendors is an alternative to the informal sector for those who cannot find a job due to the relative ease of entering and leaving the informal sector because there are no specific regulations that require it. This study aims to find out to analyze income during the Covid-19 pandemic and the New Normal street vendors selling Padang lontong vegetables which are located around the traditional 16 ilir market in Palembang City. The research method in this study is quantitative descriptive analysis of tools and technology with survey data collection techniques and documentation interviews and literature studies to determine the input and output income of Padang lontong vegetables sellers from the level of profit / loss taken by income data from street vendors who sell typical lontong vegetables. the city of Padang from the Covid-19 pandemic in March 2020 to the new normal period which is estimated to be until March 2021. Based on the analysis and discussion of the results of interviews with informants related to the impact of the Pandemic on the income of lontong vegetable street vendors, Padang Traditional Market 16 Ilir City of Palembang So it can be concluded that the Covid-19 outbreak has an impact on the income of street vendors of Lontong Vegetable Padang Traditional Market 16 Ilir City of Palembang. Profit Level 4, Padang vegetable lontong street vendors from discussions and analysis during the pandemic experienced losses. Like Mr. Babe, the profit level of Mr. Babe suffered a loss of - Rp. 6,302,333, while in the new normal period, the profit rate experienced by Mr. Babe was still experiencing losses but not as big as during the pandemic. The level of profit in the new normal is – Rp 2,253,000. Uni Ani's profit level experienced a loss of – Rp 2,609,333, while in the new normal period, the profit rate experienced by Uni Ani experienced a profit of Rp 2,115.667. Etek Cinde's profit level experienced a loss of – Rp 3,035,607, while in the new normal period the profit rate experienced by Etek Cinde experienced a profit of Rp 1,164,393. Mrs. Deswita's profit level suffered a loss of - 8,169,000, while in the new normal period, the profit level experienced by Mrs. Deswita still experienced a loss of -Rp 3,069,000. Keywords: Lontong Sayur Padang Street Vendors, Income